Inventarisasi dan Potensi Tumbuhan Berkhasiat Obat di Desa Selilau, Aru Tengah, Maluku - Sepbrilla Ananda K; Mulia Maharani; Yumaisaroh Chudaibiyah; Maria Delsiana Ndun; Jihan Fahiroh Nur Arifin; Ryan Satria Pranata; Rusdiana Tri Septiarini; Retno Wulan Devitri; Ivan Charles Seran Klau (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Indonesia has around 3,500 species of therapeutic plants, one of which is utilized by the individuals of Selilau Town, Aru Islands Rule, Maluku Area.. This study aims to examine 15 types of medicinal plants that are used traditionally, including plant parts, properties, active compound content, and pharmacological activity based on scientific literature from the last 10 years. This survey points to recognize species of restorative plants commonly utilized in neighborhood conventional medication, look at the plant parts utilized, handling strategies, and maladies treated based on neighborhood experiences and to survey logical writing to decide the dynamic compound substance and pharmacological movement of each distinguished plant. The comes about of the think about appeared that the foremost broadly utilized plant is the leaf portion. Some of them are: Momordica charantia (bitter melon) for cough; Urena lobata (pulutan) to smooth postpartum blood; Morinda citrifolia (mengkudu) for broken bones; Erythrina variegata (dadap) for body recovery; Myrmecodia pendens (ant nest) for swelling and beriberi; and Carica papaya (papaya) for malaria. Other plants such as Manihot esculenta, Tradescantia spathacea, Graptophyllum pictum, Hemigraphis alternata, Mimosa pudica, Jatropha curcas, Psidium guajava, Nypa fruticans, and Stachytarpheta jamaicensis are also used for various health complaints. Active compounds such as flavonoids, alkaloids, tannins, and saponins support pharmacological activities such as anti-inflammatory, antioxidant, antipyretic, gastroprotective, and immunostimulant. This study emphasizes the importance of documenting traditional knowledge as an effort to preserve and develop local wisdom-based medicines.